Suitability of Canopy Temperature Depression in a Temperate Climate with Drought‐Stressed Winter Rye, Determined with Three Infrared Measurement Devices. Issue 6 (19th July 2013) - Kottmann, L.; Schittenhelm, S.; Wittich, K.‐P.; Wilde, P.
Abstract: Canopy temperature has been recognised as an indicator of crop water status and may thus be a useful secondary trait in selecting for yield under dry conditions. The aim of this study was to test the suitability of canopy temperature depression (CTD =  T air  −  T canopy ) in a temperate climate with winter rye, by means of three infrared (IR) temperature measuring devices. In the years 2011 and 2012, 16 winter rye genotypes were examined under drought stress conditions in a rainout shelter and under well‐watered conditions. In each year, the CTD was determined several times during the growth period using two IR thermometers and an IR camera. By means of CTD, it was possible to detect drought stress and to differentiate between water regimes. The three measurement devices showed comparable results, despite greatly different costs. Under drought‐stress conditions, a significant positive correlation between grain yield and CTD was found on most measurement dates in 2011 and on some dates in 2012. When the CTD was pooled across water regimes, a significant positive correlation between grain yield and CTD was obtained on every measurement date. However, as genotypic differences for CTD were non‐existent, the correlations are less meaningful. The missing genotypic differences for CTD were rather caused by the limited genetic variability of the genotypes used in this study, than by climatic conditions. Due to this limitation, we were not able to make a concluding statement about the CTD in a temperature climate, although the results are quite promising and indicate that the CTD can potentially be used in a temperate climate.